Corrosion Behavior of the Stir Zone in a Friction Stir Welded Dissimilar Joint of 2024 Aluminum to AZ31 Magnesium Alloys - C. Liu (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
Corrosion behavior of the stir zone in a friction stir weld of dissimilar A12024/AZ31 alloys was investigated in the immersion test in distilled water (pH=6) for different times. Microstructures and the distribution of chemical elements were analyzed by scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS). Due to the difference in the corrosion potentials between A12024 and AZ31, the AZ31 alloy constituent in the stir zone was susceptible to the corrosion attack in the distilled water. The corrosion attack was found to occur in the narrow region of the AZ31 alloy adjoining the A12024 region, where there was a low ratio of anode-to-cathode surface area. The corrosion attack became more severe in the AZ31 alloy regions with increasing immersion time. The A12024 alloy region in the stir zone of the weld was protected by cathodic reactivity due to sacrificial anode AZ31 alloy.